Frequency of Thyroid Nodules among Patients with Colonic Polyps. (15th November 2011) - Duran, Cevdet; Gokturk, Huseyin Savas; Kulaksizoglu, Mustafa; Bakdik, Suleyman; Unler, Gulhan Kanat; Erbayrak, Mustafa; Ozkaya, Guven; Pamuk, Baris Onder; Gonen, Mustafa Sait
Abstract : Aim . Colonic polyps and thyroid nodules are common diseases and their frequency increases with age. In the literature, there is no study investigating the coexistence of colonic polyps and thyroid nodules. Therefore, this study was designed to investigate thyroid nodule prevalence in patients with colonic polyps. Material and Methods . Sixty-six patients with colonic polyps and 146 patients without colonic polyps enrolled into the study. Age and sex matched control group was composed from patients without colonic polyps. Colonoscopic examinations, thyroid ultrasonographies were performed in all patients, and TSH were measured. Results . Male/female ratio in polyp and control groups were 40/26 versus 68/78, respectively (P = 0.058 ). Mean ages were similar in both groups (53.3 ± 11.4 versus, 51.8 ± 11.4, P = 0.373 ). Thyroid nodule was detected in 44 (66.7%) patients with polyps and in 61 (41.8%) controls (P = 0.001 ). Patients with adenomatous polyps had 5 or more thyroid nodules compared to patients with hyperplastic polyps (P = 0.03 ). Thyroid nodules were more prevalent among patients aged 50 or older compared to 50 years or less (P = 0.023 ). Conclusion . Thyroid nodules were detected more common in patients with colonic polyps. Further studies are needed to clarify this coexistence.